(untitled) (Journal Of Educational and Psychological Researches, 2013)
Aim of the current research is to know: - 1 - mental loneliness among university students. 2 - personal attributes according to the model of the list of top five factors of personality among the students of the university. 3 - differences in mental loneliness by variable sex (male - female) 4 - Differences in the top five factors of personality variable by sex (male - female). 5 - The relationship between loneliness psychological and personality traits according to the model of the list of top five factors of personality among the students of the university. To achieve this used researcher scale Badri (2010) to feel loneliness and list five factors grand figure of Costa and Macri and conducted Ptribha Ansari (1997) after confirmation of _khasaúsma psychometric terms of validity and reliability, and dish scales on a sample of university students numbered (200) students selected interim random manner and in a manner equal distribution. The results showed that the students do not have a sense of loneliness, and university students Atzmon Banbsatih, openness and good and vital conscience nor Atzmon Balasabih, no significant differences between males and females in the sense of loneliness and any other factor of five factors of personality, as results showed that Extraversion and good and openness and vitality of conscience have a negative relationship function either neurotic, they linked to a sense of loneliness positive relationship function, and in light of this researcher reached some conclusions and put some of the recommendations and proposals to complement the current search.